DC and AC conductivity and dielectric properties of the metal-radical compound: Aqua[bis(2-dimethylaminomethyl-4-NIT-phenolato)]copper(II) - Yakuphanoğlu, Fahrettin; Aydogdu, Y; Schatzschneider, U; Rentschler, E (Pergamon-Elsevier Science Ltd, 2003)
The AC and DC conductivity and dielectric properties of the crystalline metal-radical compound aqua[bis(2-dimethylaminomethyl-4-NIT-phenolato)]copper(II) have been investigated. The DC electrical measurements show that the compound is a typical semiconductor with moderate activation energy E-a = 0.56 eV and at room conductivity sigma(25) = 1.38 X 10(-6)S cm(-1) as its electrical conductivity increases with increasing temperature. The AC conductivity of the sample is found to be proportional to omega(s). The temperature dependence of both the AC conductivity and the frequency exponent s is reasonably well interpreted in terms of the correlated barrier hopping model. The dielectric properties have been investigated as a function of frequency and temperature. Values of the dielectric constant epsilon' and dielectric loss epsilon were found to decrease with frequency and increase with temperature. The effect of different temperatures on the AC conductivity and dielectric properties was also investigated. The AC conductivity and values of the dielectric constant increase with increasing temperature. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: semiconductor compound; dielectric properties; electrical conductivity